Organophosphorus pesticide residues in the production chain of broccoli (Brassica oleracea L. var. italica) and cauliflower (Brassica oleracea L. var. botrytis) in Colombia: approach to risk profile (2018)
Crucifers are affected by phytosanitary problems, derived during the use of pesticides as a management strategy. Scientific and technical information on the presence of residues of organophosphorus pesticides in foods was compiled, along with the associated health effects. The production chain for broccoli and cauliflower in Colombia was also considered to characterize the risk of this danger to consumers, following the FAO methodology for creation of risk profiles in food safety. It was found that, in Colombia, the most commonly used organophosphorus pesticides are parathion, methamidophos, diazinon, chlorpyrifos and malathion, which could be present as residues in the studied crucifers. Within the review, there was no information specifically associated with the concentration of organophosphorus pesticide residues in broccoli and cauliflower from Colombia. The risk for the population was determined using residue concentration data in broccoli from studies reported in Mexico and Ecuador and information on the use of pesticides from Corpoica reports. The consumption data were extracted from ENSIN 2005. The safety risk determined for the studied food hazard was low, showing that the estimation only considered the presence of diazinon and chlorpyrifos residues in the studied matrices. It is necessary to note that this is an approximate risk profile for the two pesticides described and; specifically, in broccoli and cauliflower.